A Re-Examination of the Import Structure of India - Peera, Nurali (The Review of Economics and Statistics, 1970)
None of the added coefficients was significant at the 0.05 level, so there is no strong evidence of substantial cyclical variability in the relation between ANHWI and AU. The most one can detect is some indication of a shift during the expansion of early 1955. We take this opportunity to report the performance of our model during the past few years as a predictor of NHWI.1 The predicted and actual values of A1NHWI are shown below. Averaging quarterly predictions smooths the results. Nevertheless, the equation does not seem to have drifted systematically off course since the sample period. It over-predicted ANHWI in 1966, 1967, and 1969, and under-predicted in 1965 and 1968. However, the cumulative under-prediction slightly exceeded the over-prediction. In summary, we continue to believe that the relationship between the change in normalized help-wanted advertising and the change in unem-